PENERAPAN MEDIA PEMBELAJARAN INTERAKTIF UNTUK MENINGKATKAN PEMAHAMAN NORMA DALAM KEHIDUPAN SEHARI-HARI PADA SISWA SEKOLAH DASAR KELAS V - Siti Munawaroh; Rakhmawati Mulyani; Susilo Tri Widodo; Estherina Ratih Isnawang Wulan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to describe the application of an interactive learning model to improve elementary school students' understanding of norms in everyday life. The background of this study is based on students' low understanding of various types of norms and their application in social contexts, both at school and at home. This study uses a qualitative method with a case study type, focusing on the learning process in one class as a single research context. Data were collected through in - depth observations during learning, interviews with students, and documentation of student activities and work results. The results show that the application of an interactive learning model can provide a more meaningful learning experience for students, marked by an increase in their ability to recognize types of norms, explain the function of norms, and apply them in everyday situations. In addition, students appeared more active, enthusiastic, and able to work together during the learning process. These findings confirm that an interactive learning model can be an alternative, effective learning strategy in strengthening elementary school students' understanding of norms.